Injectable crosslinked HA hydrogel: a promising carrier for cell transplantation to treat stable vitiligo - Qianren Zheng; Jie Chen; Yixun Huang; Weikai Chen; Dandan Cheng; Qianqian Jia; Meiqin Zhu; Youguo Liao; Qiulin He; Qiulin He; Shunli Wu; Shunli Wu (Frontiers in Medicine)
Stable vitiligo significantly impacts patients’ quality of life and presents a considerable challenge to healthcare providers. In recent years, cell therapy has emerged as a promising treatment for stable vitiligo, which is demonstrated encouraging results. Among current cell-based therapies, autologous epidermal cell transplantation is regarded as a safe and cost-effective strategy. However, the therapeutic outcome critically depends on the retention and viability of the transplanted cells at the target site. Therefore, there is an urgent need to develop novel strategies to improve cell retention and maintain cell viability for improving therapeutic efficacy. In this work, a novel cell extraction method was first developed with deal with 2 h at 37°C to obtain epidermal cells while maintaining high cell viability. Subsequently, the crosslinked hyaluronic acid (HA) by BDDE was utilized as 3D scaffold for cell delivery to treat stable vitiligo. By combining the new extraction method with the HA-based hydrogel scaffold, we achieved prolonged cell retention without compromising cell viability. This approach provides a promising, time-saving strategy for treating stable vitiligo using autologous epidermal cells.